Analysis of Cytoplasmic Effects and Fine-Mapping of a Genic Male Sterile Line in Rice - Qin, Peng (Public Library of Science, 2013)
Cytoplasm has substantial genetic effects on progeny and is important for yield improvement in rice breeding. Studies on the cytoplasmic effects of cytoplasmic male sterility (CMS) show that most types of CMS have negative effects on yield-related traits and that these negative effects vary among CMS. Some types of genic male sterility (GMS), including photo-thermo sensitive male sterility (PTMS), have been widely used in rice breeding, but the cytoplasmic effects of GMS remain unknown. Here, we identified a GMS mutant line, h(2)s, which exhibited small, white anthers and failed to produce mature pollen. Unlike CMS, the h(2)s had significant positive cytoplasmic effects on the seed set rate, weight per panicle, yield, and general combining ability (GCA) for plant height, seed set rate, weight per panicle, and yield. These effects indicated that h(2)s cytoplasm may show promise for the improvement of rice yield. Genetic analysis suggested that the phenotype of h(2)s was controlled by a single recessive locus. We mapped h(2)s to a 152 kb region on chromosome 6, where 22 candidate genes were predicted. None of the 22 genes had previously been reported to be responsible for the phenotypes of h(2)s. Sequencing analysis showed a 12 bp deletion in the sixth exon of Loc_Os06g40550 in h(2)s in comparison to wild type, suggesting that Loc_Os06g40550 is the best candidate gene. These results lay a strong foundation for cloning of the H(2)S gene to elucidate the molecular mechanism of male reproduction.